ANALISIS RUTE DAN BIAYA PADA DISTRIBUSI PRODUK BENANG DI PT SPMI DENGAN MENGGUNAKAN METODE SAVING MATRIX - Janatul Nasya Rhamdani; Naufal Fadurahman Munigar; Nindi Dwi Untari; Muchammad Fauzi (LPPM Universitas Bina Bangsa, 2023)
PT Sinar Panca Mitra Indonesia (SPMI) was founded in 2011, and this company is engaged in the textile sector (small - medium business). The company has three divisions namely Multihead Division (fabric), Tricod Division (fabric) and Twisting Division (yarn). Based on the data, PT SPMI has two box cars as distribution media to consumers. However, the use of two boxcars is considered to be less effective and efficient because one of the two boxcars only delivers to one point. The research results show that by applying the Saving Matrix Method, PT SPMI can save on the number of vehicles, number of workers, delivery time and expenses. The initial fee is Rp. 262,520 for each time a delivery is made to Rp. 212,316. Where the PT SPMI company can make savings of Rp. 50,204 every time you make a delivery